Pengembangan Platform Berbagi Buku Digital Berbasis Web Menggunakan Framework Laravel - Fakhri Alauddin Tarihoran; Muhammad Irwan Padli Nasution (OKTAL : Jurnal Ilmu Komputer dan Sains, 2026)
The development of information technology has encouraged the digitalization of literacy through the use of web-based digital books. However, most existing digital book platforms are still one-way systems and do not actively encourage user participation. This study aims to design and implement a web-based digital book sharing platform called OpenBook, which allows users to act as both consumers and contributors. The platform is developed using the Laravel framework and applies a credit system as an incentive mechanism for uploading and downloading digital books. The research method used is the System Development Life Cycle (SDLC) with the Waterfall model. Black-box testing results show that all main system features function properly and meet the specified requirements.